2014
DOI: 10.1177/0305735614543283
|View full text |Cite
|
Sign up to set email alerts
|

A Turkish adaptation of a self-regulated practice behavior scale for collegiate music students

Abstract: The purpose of this study was to examine the validity and reliability of a Turkish version of a Self-Regulated Practice Behavior Scale (SRP) for college students. The scale included measures of the theoretical constructs Social Influences, Method, Behavior, and Time management as sub-scales. The original SRP is a self-report instrument that was designed to measure the self-regulated practicing behavior of intermediate instrumental music students. An adaptation and Turkish translation of the scale for collegiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 42 publications
2
19
3
Order By: Relevance
“…The Motive and Method sub-scales demonstrated the strongest internal consistency estimates (α = .85 and .83, respectively), as in Miksza (2012). However, while the sub-scale Social influence achieved the lower internal consistency in Miksza (2012), we found Time management and Behaviour with the lower estimates (α = .71 and α = .72), in correlation with Ersozlu and Miksza's (2015) study. In general, the reliability estimates found in the current study are close to those reported by Miksza (2012).…”
Section: Test Preferred Rivalsupporting
confidence: 50%
See 3 more Smart Citations
“…The Motive and Method sub-scales demonstrated the strongest internal consistency estimates (α = .85 and .83, respectively), as in Miksza (2012). However, while the sub-scale Social influence achieved the lower internal consistency in Miksza (2012), we found Time management and Behaviour with the lower estimates (α = .71 and α = .72), in correlation with Ersozlu and Miksza's (2015) study. In general, the reliability estimates found in the current study are close to those reported by Miksza (2012).…”
Section: Test Preferred Rivalsupporting
confidence: 50%
“…Although fit statistics were generally accurate for several compared factor structures, the best fit was a four-factor model (CFI = .94, SRMR = .07, RMSEA = .05, χ 2 = 1,881.89, df = 939). The other models’ fit statistics can be found in Miksza (2012) and Ersozlu and Miksza (2015). When comparing the competitor models, the results showed that the four-factor model, which included self-efficacy, combined method/behaviour, time management, and social influences, yielded the best fit to the data (Ersozlu & Miksza, 2015; Miksza, 2012).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Self-Regulated Practice Behavior Scale (SRPB) of Ersozlu and Miksza (2014) was used to measure self-regulation in music practice. The scale coefficient Alpha Cronbach was 0.85, therefore the scale reliability was considered good.…”
Section: Instrumentsmentioning
confidence: 99%